(untitled) (Annals of Bangladesh Agriculture, 2021)
Farmers in the Chattogram Hill Tracts, Bangladesh have been growing cotton (Gossypium hirsutum L.) in their traditional system of jhum cultivation which is undergoing transformation. Growing rainfed cotton as a monocrop in the uplands is constrained by farmers’ socio-economic conditions and erratic rainfall. Shifting growing season to post-monsoon dry monthscould be an option to sustain cotton production in hilly areas. An exploratory experiment was conducted for two seasons to explore the possibility of growing cotton in valley lands in Bandarban during dry season. Growth and yield potentials of dry season cotton were evaluated in relation to prevailing environmental conditions. Night temperature dropped to 9oC on several occasions in 2018-2019 season; but it remained higher than 11oC throughout the season in 2019-2020. In 2018-2019, day temperatures surged higher past March 15 occasionally exceeding 38oC. Variability in temperatures was more in 2018-19 while average temperatures were higher in 2019-20 season. Rainfall distribution was almost similar in both the growing seasons receiving total rainfall of 757 mm and 579 mm in two seasons, respectively. Higher seed cotton yield (2,047 kg per ha) was recorded for 15 November planted crop compared with 1 December planted crop (1,186 kg per ha). December 1 planted crop was affected more by low temperatures at seedling stage resulting in poor growth and fewer bolls per plant. Late planted crop was more vulnerable to rain damage at boll opening stage. Crops of both the seasons encountered high temperatures (>32oC) during boll development. Changing climate, shorter winter season and rising temperatures may allow cotton production in valley lands shifting growing season from rainy season to post-monsoon dry months. However, the window of dry season cotton growing in Bandarban, Bangladesh seems narrow. Rainfall pattern restricts planting seeds prior to mid-November. Again, high temperatures stress in March and April synchronizing boll development, and rainfall toward late April and May during boll opening may cause yield loss. Development and adoption of short duration, low temperature tolerant upland cotton varieties might be of advantage for adapting to climate change vulnerabilities. Ann. Bangladesh Agric. (2020) 24(2): 1-14